2019
DOI: 10.1007/s10706-019-00989-9
|View full text |Cite
|
Sign up to set email alerts
|

Refined Approaches for Estimating the Strength of Rock Blocks

Abstract: Micro-discrete fracture networks (lDFNs) have been integrated into grain-based models (GBMs) within the numerical software UDEC to assess rock block strength through a series of unconfined compressive strength (UCS) tests of progressively larger in size numerical specimens. GBMs were generated by utilizing a Voronoi tessellation scheme to capture the crack evolution processes within the intact rock material, and lDFNs were separately created and embedded into the GBMs to simulate the effect of preexisting defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A Trigon approach developed by Gao et al ( 2015 ) was used to generate blocks in the model, as this approach can be capable of reproducing the natural fracturing processes (e.g., crack initiation, propagation, and coalescence) of rock masses without adopting complicated constitutive models (Chen et al 2016 ; Hu et al 2020 ; Stavrou et al 2019 ; Yang et al 2017 ). In the Trigon approach, a rock mass is represented as an assembly of triangular blocks bonded together by contacts (Gao et al 2015 ).…”
Section: Numerical Modelingmentioning
confidence: 99%
“…A Trigon approach developed by Gao et al ( 2015 ) was used to generate blocks in the model, as this approach can be capable of reproducing the natural fracturing processes (e.g., crack initiation, propagation, and coalescence) of rock masses without adopting complicated constitutive models (Chen et al 2016 ; Hu et al 2020 ; Stavrou et al 2019 ; Yang et al 2017 ). In the Trigon approach, a rock mass is represented as an assembly of triangular blocks bonded together by contacts (Gao et al 2015 ).…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The large range in the physical and mechanical properties typically observed for volcanic rocks of the same porosity is often considered to be the result of microand sample-scale heterogeneities (e.g., Heap and Violay, 2021). Numerical experiments using modelling software Fast Lagrangian Analysis of Continua (FLAC; Itasca Consulting Group Ltd) (Villeneuve et al, 2012), UDEC and 3DEC (Distinct Element Modelling; Itasca Consulting Group Ltd) (Ghazvinian et al, 2014;Stavrou et al, 2019;Xu et al, 2020), Rock Failure Process Analysis (RFPA; Mechsoft Technology) (Tang et al, 2000(Tang et al, , 2007Zhu, 2008), and Particle Flow Code (PFC; Itasca Consulting Group Ltd) (Peng et al, 2017;Liakas et al, 2017) have also demonstrated that microstructural heterogeneity leads to a reduction in rock strength. Numerical experiments have also shown that pore size and shape (Heap et al, 2014b;Griffiths et al, 2017;Heap et al, 2021c) and crystal content (Heap et al, 2016) can influence mechanical behaviour of volcanic rocks.…”
Section: Introductionmentioning
confidence: 99%
“…DEM GBMs have also proven to be a useful tool to scale the mechanical behaviour of intact rock at the laboratory scale to the behaviour of rock blocks at an engineering scale (Stavrou and Murphy 2018;Stavrou et al 2019). The effects of thermo-mechanical loading have also been demonstrated in GBMs.…”
Section: Introductionmentioning
confidence: 99%